Prévalence De La Douleur Neuropathique Chez Des Patients Souffrant De Lomboradiculalgie Commune En Consultation Rhumatologique À Lomé (Togo) - Kakpovi, Kodjo; Tagbor, Komi Cyrille; Fianyo, Eyram; Doleagbenou, Agbeko Komlan; Guinhouya, Kokou Mensah; Koffi-Tessio, Viwalé Etonam Sika; Houzou, Prénam; Kpelao, Essossinam; Belo, Mofou; Oniankitan, Owonayo; et al. (European Scientific Journal, ESJ, 2017)
Objective: To determine the prevalence and factors associated with neuropathic pain in patients with non-specific low back pain. Methods: This was a cross-sectional study conducted from May to July 2016 in the Rheumatology, Neurology and Neurosurgery departments of Lome. The DN4 questionnaire was used for the diagnosis of neuropathic pain in the 200 patients with low back pain included in this study. Results: Of the 200 patients (147 women and 53 men) included in the study, neuropathic pain was present in 92 (46%). The average age of the 92 patients (67 women vs 25 men, p = 0.04) was 55.5 ± 12.4 years (women 55.2 ± 12.8 vs. men 54.6 ± 11.4, p = 0.5). The characteristics of neuropathic pain mainly found were: burning sensation (n = 67, 72.8%); electrical discharges (n = 64, 69.6%); tingling (n = 90; 97.8%); tickling (n = 57; 62%); numbness (n = 89; 96.7%); hypoesthesia (n = 52; 56.5%). Factors significantly associated with the presence of neuropathic pain in LBP were age (p = 0.005), duration of LBP (p = 0.04), high blood pressure (p = 0.001), radicular pain (p = 0.00002) and the past history of the LBP (0.000000). Conclusion: Neuropathic pain is common in patients with LBP at Lome. The duration of LBP, past history of LBP, previous NSAID use, BMI, pain severity and radicular pain appear to be predictive of the occurrence of these neuropathic pains.